Developing Adaptive Project Construction Cost Control Using Multi-Nonlinear Regression Engineering Techniques - Maaroof Maaroof, Maaroof Aqeel; Naimi, Sepanta (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Construction project management using the techniques of multi-nonlinear regression method was the branch that the study dealt with in its pathway. The study identified and evaluated the impact of various factors like the project elements including the building specification impact, the building location effect, the soil effect, and the construction process factor impacts. on the cost of the project. the study analyzed the data toward building an effective model based on multi-nonlinear regression method for controlling the project from the initial phase toward the final implementation stage. The study outline was to reach adaptive management of the construction project under the conditions in Iraq to enhance the performance of the management team in the construction sector. The findings show that using a project control’s actual values improves project management teams’ capacity to recognize cost and schedule concerns on time.